2003
DOI: 10.1097/00000421-200304000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Biweekly Docetaxel and Vinorelbine in Anthracycline-Resistant Metastatic Breast Cancer

Abstract: The aim of this study was to determine the efficacy and toxicity of a biweekly combination of docetaxel and vinorelbine in patients with metastatic breast cancer (MBC) previously treated with anthracyclines. Eligible patients (n = 49) with MBC received vinorelbine, 25 mg/m2, followed by docetaxel, 60 mg/m2. Cycles were repeated every 14 days for a total of 8 planned cycles. Response rate was evaluated every 4 cycles. All 49 patients were evaluable for safety and 44 for efficacy. Vinorelbine plus docetaxel resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 11 publications
1
9
0
Order By: Relevance
“…In addition, literature data have reported interesting results, probably because of a synergistic effect, when using the 2 drugs in combination. [22][23][24][25][26][27][28][29][30][31][32] The efficacy results observed in the present study are in line with those of previous experiences with the same regimen as reported in Table 4. [22][23][24][25][26][27][28][29][30][31][32] Our data report a 51% ORR with a 17% CR rate and a median survival of 14 months in a series of patients with visceral metastases and heavily pretreated once again confirming the value of the combination of DCT and VNR in the treatment of MBC.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In addition, literature data have reported interesting results, probably because of a synergistic effect, when using the 2 drugs in combination. [22][23][24][25][26][27][28][29][30][31][32] The efficacy results observed in the present study are in line with those of previous experiences with the same regimen as reported in Table 4. [22][23][24][25][26][27][28][29][30][31][32] Our data report a 51% ORR with a 17% CR rate and a median survival of 14 months in a series of patients with visceral metastases and heavily pretreated once again confirming the value of the combination of DCT and VNR in the treatment of MBC.…”
Section: Discussionsupporting
confidence: 90%
“…Finally, noteworthy is that no toxic deaths have been recorded. These data are definitely more favorable as compared with those of other experiences, [22][23][24][25][26][27][28][29][30][31][32] particularly with respect to the study by Kornek et al 23 that reported an high incidence of peripheral neurotoxicity (42%) and hematological toxicity with septic complications notwithstanding the use of G-CSF. It is very likely Treating Metastatic Breast Cancer that the differences in safety profile are ascribable to the different treatment schedule since we delivered VNR only on day 1 of each cycle, instead of days 1 and 8 as reported in other experiences.…”
Section: Discussionmentioning
confidence: 65%
“…For example, a paclitaxel concentration of 10 nm is only 1/10 to 1/ 100 of the concentration achieved in patient serum after a single therapeutic dose of about 200 mg/m 2 (Pulkkinen et al 1996). Several recent reports from our group and others suggest that combinations of vinorelbine with paclitaxel or docetaxel are promising in patients with advanced lung, breast, and ovarian cancer (Kourousis et al 1998;Grunberg et al 1999;Ginopoulos et al 2002;Aravantinos et al 2003;Gomez-Bernal et al 2003). Temporal and sequencing effects of administration of vinorelbine and paclitaxel on drug efficacy and toxicity may also be important (Knick et al 1995;Budman et al 1996;Chang et al 1996;Sanchez et al 2002;Airoldi et al 2003).…”
Section: Discussionmentioning
confidence: 95%
“…All disease sites responded to treatment, even if the small sample size precludes any firm conclusion about the relative occurrence of responses according to sites of disease. The median overall survival of 28.7 months is noteworthy, which is longer than that commonly reported with other regimens including docetaxel [4,11,12,13,21,22,23,24]. Treatment appeared to be slightly more active in previously anthracycline-‘exposed’ patients (response rate 50%) in comparison with ‘resistant’ patients (response rate 29%), even if the small sample size precludes any definite conclusion.…”
Section: Discussionmentioning
confidence: 70%